2015
DOI: 10.3389/fpubh.2015.00180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates for Psychosocial Distress Among In-School Adolescents in Zambia

Abstract: There is scanty information on correlates for psychosocial distress in Zambia. Secondary analysis was conducted using the data collected in 2004 in Zambia during the global school-based health survey to determine the prevalence and correlates for psychosocial distress. Logistic regression analyses were used to estimate magnitudes of associations between exposure factors and the outcome, while the Yates’ corrected Chi-squared test was used to compare proportions at the 5% significance level. A total of 2257 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
44
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 19 publications
(27 reference statements)
13
44
4
Order By: Relevance
“…Leadbeater & al found that this phenomenon could be explained by the greater emphasis girls place on interpersonal relationships in comparison to boys [21]. Like Siziya & al [10], we did not find an association between gender and psychological distress in adolescents. This can be explained by the differences in the stress management strategies boys and girls use, as boys tend to be more detached from their emotions and difficult situations and to be more emotionally inhibited than girls [22].…”
Section: Ssociated Factorscontrasting
confidence: 61%
See 4 more Smart Citations
“…Leadbeater & al found that this phenomenon could be explained by the greater emphasis girls place on interpersonal relationships in comparison to boys [21]. Like Siziya & al [10], we did not find an association between gender and psychological distress in adolescents. This can be explained by the differences in the stress management strategies boys and girls use, as boys tend to be more detached from their emotions and difficult situations and to be more emotionally inhibited than girls [22].…”
Section: Ssociated Factorscontrasting
confidence: 61%
“…Having close friends was a protective factor against psychosocial distress. This result was confirmed by Siziya & al [10]; close friends should always be there to share their concerns and this would avoid distress. For girls, our study showed the extent of psychosocial distress in rural areas; this can be explained by the social pressures still current in rural areas where girls are often minimized or forced to be quickly socially productive either by getting married or having income-generating activities.…”
Section: Ssociated Factorssupporting
confidence: 60%
See 3 more Smart Citations